JURIDICAL ANALYSIS OF THE JUDGE'S DECISION IN THE CASE OF PROTECTED ANIMALS AT THE DENPASAR DISTRICT COURT - Wiratny, Ni Ketut; Sihotang, Erikson; Widyatmika , Ida Bagus Ary (International Journal Multidisciplinary (IJMI), 2026)
Objective: To analyze the considerations and inhibiting factors in criminal cases regarding protected animals in the Denpasar District Court, specifically in Decision Number 809/Pid.Sus/2024/PN Dps. Method: The case is analyzed based on the judge's considerations, including elements of intentionality, the defendant's ignorance, incorrect application of cumulative articles, and the use of justice and societal usefulness in decision-making. Results: The judge's considerations focused on intentionality, ignorance of the legal requirement for permits, and the application of the wrong articles. The defendant was not found guilty of committing a criminal act as the judge balanced legal certainty with justice and societal impact. Novelty: The case highlights the impact of outdated legislation, lack of coordination among law enforcement agencies, and the role of social media in facilitating the trade of protected animals.